2017
DOI: 10.1016/j.surfcoat.2017.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cr additions on the structure and oxidation resistance of multilayered TiAlCrN films

Abstract: Ti 1−x Al x N coatings with NaCl-type structure have been widely used in advanced machining and other high temperature applications due to their excellent mechanical, thermal and tribological properties. Here, we investigated the influence of Cr additions on the structure, mechanical properties and oxidation resistance, including the oxide scale characterization, of multilayered TiAlN/CrAlN coatings deposited by magnetron sputtering. The properties of Cr rich coatings were compared to a TiAlN film deposited as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Recently, the groups of T. Polcar and A. Cavaleiro performed studies on the addition of Cr to the Ti-Al-N system and its influence on thermal resistance, oxidation stability, tribological and cutting performance by the deposition of quaternary Ti-Al-Cr-N coatings [121,122]. A coating which demonstrates relatively low wear resistance at room temperature (Ti-Al-Cr-N system) in comparison to the other (in this case, the Ti-Al-N system) can exhibit much higher wear performance at elevated temperatures (650 • C) corresponding to realistic conditions for cutting tools' working temperatures.…”
Section: Multi-elemental Compounds and High-entropy Alloy Protective mentioning
confidence: 99%
“…Recently, the groups of T. Polcar and A. Cavaleiro performed studies on the addition of Cr to the Ti-Al-N system and its influence on thermal resistance, oxidation stability, tribological and cutting performance by the deposition of quaternary Ti-Al-Cr-N coatings [121,122]. A coating which demonstrates relatively low wear resistance at room temperature (Ti-Al-Cr-N system) in comparison to the other (in this case, the Ti-Al-N system) can exhibit much higher wear performance at elevated temperatures (650 • C) corresponding to realistic conditions for cutting tools' working temperatures.…”
Section: Multi-elemental Compounds and High-entropy Alloy Protective mentioning
confidence: 99%
“…2, a). The formation of such fine crystallites is associated with the presence of about 65-70 at.% Al, which is known to improve the structure of TiN and prevent the formation of highly columnar morphology [9]. When activating the Cr targets and rotating the substrate holder, TiAlCrN (I) and (II) multilayer coatings are formed (Fig.…”
Section: Microstructure Of Samplesmentioning
confidence: 99%
“…One of the possible solutions of this problem is the formation of nanostructures as nanocomposites in them, which will provide better toughness and improve the general mechanical characteristics of such thin films [5,6]. In particular, experimental studies [7,8] showed that nanostructured TiAlN nitrides have better functional characteristics and increased thermal and chemical stability compared to monolithic films (single layers) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…(Ti,Cr)N has been attracting more attention owing to high hardness (4000 HV), high temperature oxidation resistance (600°C), and low friction coefficient (0.3) [9,10] Thermal annealing of Cr1-xAlxN coatings up to 900 °C induces a transformation towards their stable phases of wurtzite (w-) AlN, and then cubic (bcc-) Cr via intermediate phase of hexagonal (h-) Cr2N with concomitant N-loss, and thereby causes a deterioration of the mechanical properties [11]. Compared with TiN and (Ti,Al)N coating, (Ti,Al,Cr)N coating gets more attention due to its higher hot hardness and oxidation resistance [12,13] M. Danek [14] reported that the increase of Cr contents in TiAlCrN coating could significantly enhance the oxidation resistance.In order to avoid brittle failure due to cracking, wear-resistant coatings must be both hard and tough. Based on these criteria, Ou et al [15] reported in a first principles study of the elastic properties of Ti1-xTMxN alloys (TM = Y, Zr, Nb, Hf, and Ta) that TiN highly alloyed with NbN or TaN exhibits significantly improved ductility.…”
Section: Introductionmentioning
confidence: 99%